CURRENT STATUS OF CAREGIVER BURDEN AMONG STROKE PATIENT CAREGIVERS IN THE EMERGENCY AND STROKE DEPARTMENT, NATIONAL GERIATRIC HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the characteristics of caregivers and the level of caregiver burden in Vietnam, and to identify associated factors. Subjects and Methods: A cross-sectional study was conducted on 137 caregivers. Demographic and clinical information was collected, and caregiver burden was assessed using the Zarit Burden Interview. Sleep quality was measured using the PSQI, and patient dependence was evaluated using the ADL/IADL scales. Results: The majority of caregivers were aged 40–60 years (69.3%), 55.5% were female, 94.9% were married, 76.6% had a university degree or higher, and 74.5% lived in urban areas. Most caregivers experienced low to moderate burden (88%), while only 11.2% had moderate to high burden. Comparing caregiver burden levels, PSQI scores were significantly higher in the high-burden group than in the low-burden group (6.5 vs. 3; p = 0.001), whereas age, gender, marital status, and ADL/IADL scores showed no significant differences. Conclusions: Most caregivers adapt well to their caregiving role. The low burden may be related to higher educational levels, better health literacy, and East Asian cultural values, where caring for relatives is considered a responsibility and duty. Sleep quality was strongly associated with caregiver burden, while the patient’s physical dependency was not a determining factor. Caregivers with high burden should be screened and provided with psychological support and opportunities for rest.